Marietta Anca. A Portrait of a Lady - SINIGAGLIA, Lucian (Studia Universitatis Babeș-Bolyai Dramatica, 2018)
Marietta Anca was not the only artist to catch the eye of a number of personalities who wrote about theater. Alice Voinescu, Camil Petrescu, Mihail Sebastian, N. Carandino, Lucia Demetrius, Ioan Massoff, Petre Comarnescu have left testimonies about the artists who were at the heart of Bucharest’s theatrical life. Their opinions, read with maximum possible objectivity, make up the portrait of an artist with a vigorous personality, over whom a veil had settled, seemingly inexplicably, since the last years of her career. She was in demand and she excelled in historical evocation tragedy and in the modern psychological analysis drama.